2013
DOI: 10.1074/jbc.m113.471433
|View full text |Cite|
|
Sign up to set email alerts
|

Maternal Embryonic Leucine Zipper Kinase (MELK) Reduces Replication Stress in Glioblastoma Cells

Abstract: Background: Protein kinase MELK is expressed at very high levels in glioblastomas, but it is not understood how this benefits tumor growth. Results: A deficiency of MELK causes replication stress and is associated with cell cycle arrest and senescence. Conclusion: MELK is required for progression through unperturbed S phase. Significance: The inhibition of MELK emerges as an attractive cancer therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
70
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(75 citation statements)
references
References 50 publications
5
70
0
Order By: Relevance
“…This, in turn, activates ATM, Chk2, and p53 sequentially causing cell-cycle arrest and accumulation of DNA damage at stalled replication forks. This same group subsequently demonstrated a similar mechanism when treating with a novel MELK inhibitor (upregulation of p21 leading to activation of ATM, Chk2, and p53) allowing the cancerous cells to continue proliferation in the presence of replicative stress (37,38). It is unclear what, if any, role this mechanism plays in radioresistance of triple-negative and basal-like breast cancers as the vast majority of these tumors, and all of the cell lines used in this study, harbor p53 mutations.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…This, in turn, activates ATM, Chk2, and p53 sequentially causing cell-cycle arrest and accumulation of DNA damage at stalled replication forks. This same group subsequently demonstrated a similar mechanism when treating with a novel MELK inhibitor (upregulation of p21 leading to activation of ATM, Chk2, and p53) allowing the cancerous cells to continue proliferation in the presence of replicative stress (37,38). It is unclear what, if any, role this mechanism plays in radioresistance of triple-negative and basal-like breast cancers as the vast majority of these tumors, and all of the cell lines used in this study, harbor p53 mutations.…”
Section: Discussionmentioning
confidence: 82%
“…Previous groups have demonstrated that in gliomas, MELK knockdown leads to cellular senescence, cell-cycle arrest, and increased replicative stress secondary to the increase in dsDNA breaks (37). This is mediated, in part, by p21 whose expression is increased by MELK depletion.…”
Section: Discussionmentioning
confidence: 99%
“…FACS analysis was performed as described previously (Kig et al, 2013). Briefly, asynchronous growing cells were induced or non-induced for 48 h. After fixation in 70% ethanol, cells were stained with 50 µg/ml propidium iodide (Sigma) and the DNA content was analyzed by cytometric analysis (Attune Acoustic Focusing Cytometer), using the Attune FACS software.…”
Section: Facs Analysismentioning
confidence: 99%
“…Immunoblotting and EGFP-trapping were performed as described previously (Kig et al, 2013;Van Dessel et al, 2010). For the immunoprecipitation of endogenous Ki67, RepoMan and Kif18A, cells were first synchronized with a single thymidine arrest, released for 5 h and incubated for 16 h with 7.5 µM S-Trityl-L-cysteine (STLC).…”
Section: Immunoprecipitationmentioning
confidence: 99%
“…In this study, the authors focus on the maternal embryonic leucine zipper kinase, or MELK, which had been previously implicated as an oncogenic kinase important for proliferation in basal-like breast cancer (10). MELK has also been shown to be important for mitosis and replicative stress in glioma stem cells (11,12), and was shown to protect glioma stem cells from radiation induced cell death (13). Previous work by the same group had identified MELK as overexpressed in TNBC (14), suggesting that it might be a potential target for this breast cancer subtype.…”
mentioning
confidence: 99%